Presurgical molecular therapy for renal cell carcinoma with venous tumor thrombus: a systematic review and meta-analysis - Chen, Kewei; Zhuo, Lin; Liu, Zhuo; Ge, Liyuan; Yu, Le; Zhang, Shudong (Frontiers in Immunology, 2025)
BackgroundPresurgical molecular therapy (PMT) including tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) showed various outcomes for renal cell carcinoma (RCC) with tumor thrombus (TT). We aimed to evaluate the impact of PMT on Mayo level or TT height and the treatment-related adverse events (AEs).MethodsA systematic literature search was conducted in PubMed, Embase, Cochrane Library, and Web of Science up to June 2023 to identify relevant studies investigating the impact of PMT on RCC patients with TT. The literature investigating the impact of PMT on RCC patients with venous TT, whether followed by surgery or not, was included.ResultsOverall, 184 patients were enrolled in this study. 30.7% (95% CI, 17.6–43.8%, I2 = 79%, p<0.01) patients experienced a decrease in TT levels after receiving PMT, while only 1.5% (95% CI, 0–0.044%, I2 = 0%, p=0.98) exhibited an increase in TT levels. An average decrease of 15.2mm (95% CI, 22.4–8.0, I2 = 77%, p<0.01) of TT in 117 patients was observed after PMT. The most common AEs was hypertension (49.9%, 95% CI, 27.1–77.7, I2 = 88%, p<0.01), diarrhea (20.2%, 95% CI, 2.7–37.6, I2 = 83%, p<0.01), fatigue (25.3%, 95% CI, 6.1–44.4, I2 = 84%, p<0.01) and hand-foot syndrome (25.5%, 95% CI, 5.6–45.5, I2 = 86%, p<0.01).ConclusionPMT is available to assist in lowering the TT level in RCC patients aiming to simply the surgical procedures, particularly in patients with Mayo grade 3/4. The frequency and severity of AEs during PMT are tolerable. Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420234399128.